Economically Optimum Design of Cusum Charts - Goel, Amrit L.; Wu, S. M. (Management Science, 1973)
We present a procedure for the economic design of Cusum charts to control the mean of a process with a normally distributed quality characteristic. A model is derived which gives the long-ran average cost as a function of both the design parameters of the chart and the cost and risk factors associated with the process. The “pattern-search” technique is employed to determine the optimum values of the sample size, the sampling interval and the decision limit. The cost surfaces are investigated, numerically, to study the effects of changes in the design parameters and in some of the cost and risk factors.